Cyclability in Japan: Toward a Comprehensive National Assessment - Lucas Belliard; Akinori Morimoto; Naohiro Kitano (Urban Science)
Japan is a unique country in terms of mobility. While the popularity of bicycles as a practical and environmentally friendly means of transport is growing worldwide, particularly since the COVID crisis, bicycle use in Japan has been declining for over 40 years. With a modal share that is still very high (around 12% of the national average), cycling is nevertheless subject to major disparities across the region, whether in terms of use, infrastructure, policies, or safety. This unique study, therefore, attempts to develop a unique methodology for assessing cyclability in Japan, tailored to its specific characteristics, and including the following factors: use and culture by focusing on the user and infrastructure and policies by focusing on planning and safety, both real and perceived. Based on a nationwide survey and a unique database, we are bringing together the realities of local areas with the opinions of hundreds of Japanese cyclists. The results show significant discrepancies between the demands/needs of cyclists and the policies, reflecting a lack of comprehensive strategies, particularly with regard to cycling infrastructure. This allows us to provide a complete and accurate picture of cyclability in Japan and the reasons for its disparities.